Impact of Industrial Structural Changes on Income Inequality Trends - Karunaratne, H. D. (My University, 2012)
The shape of the income distribution in a country is subject to change with structural changes in output and employment. Since the mid 1950s, pioneering work done by Arthur Lewis, Ranis, Fei and others, has theoretically demonstrated this phenomenon by emphasizing the dualistic features in developing countries. According to their models, a rising share of the modern sector (mainly the manufacturing industry) in terms of output and employment makes income distribution more unequal in the early stages of economic development. That is because before the Lewisian turning point occurs, labour income remains unchanged while profit income rises in the modern sector. Therefore, income distribution in developing countries can theoretically have a long term equitable shape only after the absorption of surplus labour working in the backward agriculture. …